دراسة قياسية لإرتباط مداخيل الجباية البترولية بالنمو الاقتصادي في الجزائر خلال الفترة (1970-2017) - الجودي, محمد علي; روابح, عبد الرحمن (جامعة الوادي - University of Eloued, 2021)
ارتبطت جل اقتصاديات الدول المصدرة للنفط بمداخيل الجباية البترولية، فتأثرت مؤشراتها التنموية بتقلبات أسعار النفط العالمية. لذا حاولت معظمها فك هذا الارتباط بتنويع مصادر تمويل اقتصادها، والجزائر التي يعتبر اقتصادها ريعيا بحوالي97%، حاولت البحث عن بدائل أخرى لتمويل برامجها التنموية. تهدف هذه الدراسة إلى تتبّع مدى ارتباط سعر البترول POIL والناتج المحلي الخام PIB، وتوصلت إلى نتيجة أساسية تمثلت في وجود سببية في المدى الطويل والقصير تتجه من المتغير المستقل المتمثل في الناتج الوطني الخام LPIB نحو المتغير التابع المتمثل في سعر البترول LPOIL. Most of the economies of oil exporting countries are linked to revenues of Petroleum taxation. This link led to development indicators were affected by fluctuations in international oil prices, so most of them tried to break this link by diversifying the sources of financing their economy. Algeria has tried to find other alternatives to finance its development programs, considering that its economy is rentier by about 97%. This study aims to track how the price of POIL is linked to PIB, and it reached a basic conclusion that there was causality in the long and short term, moving from the independent variable represented in the gross national product towards dependent variable represented in price of oil LPOIL.
A Standard Study Of The Correlation Of Petroleum Taxation Revenues With Economic Growth In Algeria -During The Period )2017-1970 (
مقال
Keywords: Fiscal Policy ; Petroleum Taxation ; Time Series ; Stability ; Economic Growth